2014
DOI: 10.1016/j.psyneuen.2014.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Early life maternal separation stress augmentation of limbic epileptogenesis: The role of corticosterone and HPA axis programming

Abstract: Early life stress causes long-lasting effects on the limbic system that may be relevant to the development of mesial temporal lobe epilepsy (MTLE) and its associated psychopathology. Recent studies in rats suggest that maternal separation (MS), a model of early life stress, confers enduring vulnerability to amygdala kindling limbic epileptogenesis. However, the mechanisms underlying this remain unknown. Here, we tested whether hypothalamic-pituitary-adrenal (HPA) axis hyper-reactivity induced by MS - specifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 69 publications
3
42
0
2
Order By: Relevance
“…Too many research groups are avoiding/neglecting the issue of examining sex effects in their studies, as is evident from inspection of Table 1. This is not only apparent in stress/epilepsy studies, but also many areas of neurology and psychiatry early life stress programming of HPA axis function can be ameliorated by early intervention (Ivy et al, 2010), or by intervention in adulthood (Koe et al, 2014;Weaver et al, 2005). This needs to be taken into account when designing mechanistic and treatment protocols regarding effects of early life stress on adult disease states.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Too many research groups are avoiding/neglecting the issue of examining sex effects in their studies, as is evident from inspection of Table 1. This is not only apparent in stress/epilepsy studies, but also many areas of neurology and psychiatry early life stress programming of HPA axis function can be ameliorated by early intervention (Ivy et al, 2010), or by intervention in adulthood (Koe et al, 2014;Weaver et al, 2005). This needs to be taken into account when designing mechanistic and treatment protocols regarding effects of early life stress on adult disease states.…”
Section: Discussionmentioning
confidence: 99%
“…The males in this study, but not the females also exhibited higher corticosterone levels, suggesting that this was related to the higher seizure scores and mortality. Finally, a study by Koe et al showed that female rats previously exposed to maternal separation demonstrated exaggerated corticosterone stress responses to kindled seizures, as well as a vulnerability to amygdala kindling (Koe et al, 2014). By blocking the synthesis of corticosterone, the authors were able to prevent the seizure-induced corticosterone response, and normalise kindling rates.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…of the HPA axis (4). However, few studies have tackled the role of allostatic load in adult animals and the effect on HPA axis function and implications for disease.…”
Section: Primed For Problems: Stress Confers Vulnerability To Epilepsmentioning
confidence: 99%
“…Interestingly, recent studies demonstrated that seizures themselves activate the HPA axis (4,8), and seizure-induced elevations in corticosterone levels correlated with increased depression-like behaviors (9). It is possible that the "first hit" alters HPA axis reactivity, whereby in response to the "second hit, " there is hyperexcitability of the HPA axis that contributes to increased seizure susceptibility and associated comorbidities.…”
Section: Primed For Problems: Stress Confers Vulnerability To Epilepsmentioning
confidence: 99%
See 1 more Smart Citation